PENGARUH SELF AWARENESS, ETOS KERJA, RESILIENSI, TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) DAN KINERJA TENAGA KEPENDIDIKAN DI PERGURUAN TINGGI SWASTA SURABAYA - Alfi Pratama Putra; Siti Mujanah; Nanis Susanti (STIE Mahardhika, 2022)
The purpose of this study was to examine the effect of Self Awareness, Work Ethic, Resilience, on Organizational Citizenship Behavior (OCB) and Performance of Education Personnel at private University Surabaya. The sample used in this study was 177 respondents from the employees who were from several private Universities in Surabaya. Data was collected by distributing questionnaires by google form. While the technical analysis of the data used in this study is to use Partial Least Square (PLS). The results of this study shows that Self Awareness, Work Ethic, and Resilience significantly affect on Organization Citizenship Behavior Employee Performance.